Supersonic similitude for oscillating non-planar wedge - Crasta, Asha; Khan, Sher Afghan (International Organization of Scientific Research (IOSR) Journals, 2014)
A similitude has been obtained for a pitching oscillating Non planar wedge with attached bow shock at high angle of attack in supersonic flow. A strip theory in which flow at a span wise location is two dimensional and independent of each other is being used. This combines with the similitude to lead to a one-dimensional piston theory. Closed form of simple relations is obtained for stiffness and damping derivatives in pitch. The present theory is valid only when the shock wave is attached with the nose of the wedge. From the theory developed some of the results are obtained for wide range of Mach number and angle of attack with remarkable computational ease. From the results it is found that when convexity is introduced in the non-planar wedge, this results in shifting of the center of pressure towards the leading edge, and the stiffness as well as the damping derivative decreases with the increase in the Mach number for all the values of the semi vertex angles.